National Policy Innovation Reflections: Advancing Sustainable Policies to Reducing Waste - Saputra, Anggara Setya; Kurniasih, Denok; Setyoko, Paulus Israwan (Universitas Sultan Ageng Tirtayasa, 2024)
Increasing national waste volumes are causing significant environmental and public health issues. There is a need for policy innovation to tackle waste management issues. This research aims to understand new methods that led to formulating national-level policies to reduce waste. A literature review was used as the research method to understand how policy innovation can be used further to reduce the volume of waste. Searches were made in Google Scholar and Scopus with the keywords